(untitled) (Jurnal Simki Economic, 2023)
This study aims to test whether there is an effect of Return On Assets, Return On Equity, and Asset Growth on the capital structure of beverage and food companies listed on the Indonesia Stock Exchange during 2015-2019. The sample selection using purposive sampling technique resulted in 17 manufacturing companies for 5 years starting from 2015-2019, so a total sample of 80 annual reports from beverage and food companies was obtained. From the results of the research conducted, it can be concluded that the Return On Assets, Return On Equity variables have no effect on the capital structure while asset growth has an effect on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019.